Aqueous Extract of Black Maca (Lepidium meyenii) on Memory Impairment Induced by Ovariectomy in Mice - Rubio, JL (2011)
National Nature Science Foundation of China, NSFC in 2004 (30472016/C03020701); International Technologic Collaboration Project, grant no. 2006DFA21740; Peruvian National Council of Sciences, Technology and Innovation (CONCYTEC) through the grant PROCOM 2005.